PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN: PERSPEKTIF BALANCED SCORECARD - Alviane, Geta; Purnamasari, St. Vena (Jurnal Akuntansi Bisnis, 2011)
This study examines the influence of Intellectual Capital (IC) on firm performance as measured by the perspective of Balanced Scorecard (BSC). BSC perspectives consists of 4: the cllstomer (measured by retention and clis/orner acquisition). internal business processes (measured by sales growth). learning and growth (measured by the prodllctivity of employees) and financial (measured by ROA and ROE). This stU(ZV took a sample of companies in Indonesia Slack Exchange in 2006-2009 as many as 45 companies The results showed Intellectual Capital (VAICâ¢) does not affect compan performance in terms of customer perspective of BSC. Intellectual Capital (VAICâ¢) did not affect company performance in terms of infernal business process perspective of BSC. Intellectual Capital (VAICâ¢) did not afTect company performance in terms of learning and growth perspective of BSC. Intellectual Capital (VAICâ¢) does not affect the performance of the company from the financial perspective of BSC. No significant effect of Intellectual Capital (VAICâ¢) on perfonnance due to the human resources that are not capitalized into an asset but is charged.